2020
DOI: 10.3389/fpsyt.2020.00494
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Body Composition Are Associated With Severity and Risk of Depression, and Serum Lipids

Abstract: Background: Physical activity and a healthy body composition are said to reduce the risk of major depressive disorder. Nonetheless, deeper insight is needed into which specific forms of physical activity (and their relation to body composition) are effective in improving and preventing depressive symptoms. Methods: We compared different self-reported physical activities of the Global Physical Activity Questionnaire and body composition measures between patients with a current major depressive episode (MDE; N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Two studies by Ormonde Do Carmo et al 29 and Hamidifard et al 41 reported that BMI was not associated with depressive disorder. Our findings were consistent with the results of previous studies indicating that depression was associated with weight 28 and was not associated with waist circumference 40 , 42 . Additionally, our crude model results were linked to those of previous studies suggesting that depression was related to BMI in only women 23 , 46 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two studies by Ormonde Do Carmo et al 29 and Hamidifard et al 41 reported that BMI was not associated with depressive disorder. Our findings were consistent with the results of previous studies indicating that depression was associated with weight 28 and was not associated with waist circumference 40 , 42 . Additionally, our crude model results were linked to those of previous studies suggesting that depression was related to BMI in only women 23 , 46 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, several studies argued that depression was not associated with obesity indices. Von Zimmermann et al 42 revealed that BMI, weight, height, and waist circumference were not different between the major depressive episode group and the healthy control group in German men and women. A study by Wu et al 31 suggested that BMI and waist-to-hip ratio were not associated with depressive symptoms in Chinese adults.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We analyzed human samples that were collected for the CeraBiDe (“Ceramide-associated Biomarkers in Depression”) study [ 57 , 58 , 59 , 60 ]. Here, we included MDD patients who were currently experiencing depression, were unmedicated, and had not received medication for at least 2 weeks ( n = 60) and a healthy control group ( n = 61).…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed data collected for the CeraBiDe ("Ceramideassociated Biomarkers in Depression") study (Mühle et al 2019b;von Zimmermann et al 2020;Wagner et al 2019), which was approved by the Ethics Committee of the Medical Faculty of the Friedrich-Alexander University Erlangen-Nürnberg (FAU, ID 148_13 B, 2013).…”
Section: Sample Populationmentioning
confidence: 99%